Effects of climate change on food security in Mutasa district - Sauriri, Solomon G.T. (Midlands State University, 2017)
This research seeks to highlight the Impacts of climate change on food security in Mutasa District in Manicaland Province in partial fulfilment of Bachelor of Arts Honours Degree in Development Studies at Midlands State University. The research presents the background of the study which is the impacts of climate change on food security. Research objectives and questions, limitations encountered and delimitations to the study are as well presented in this research. This study reviewed the prevailing conditions in Mutasa District resulting from climate change. It also poses an assessment of the capacity of the community’s mechanisms and other institutions in responding to the effect of climate change. The study objectives was to identify current prevailing effects of climate change in Mutasa District, to assess the impact of these effects on different age groups as well as gender based, to identify what the government and other players are doing in helping the community resilience capacity on climate change and give possible solutions in form of recommendations that can be useful in adapting to this problem or reduce the impact in form of mitigation recommendations. Interviews, questionnaires and observations were used to collect data in Mutasa for the fulfilment of the objectives and answer the research questions. The study showed that the community is suffering much from climate change and their coping muscle is tender to curb the devastating effects of climate change since the majority s poor and depend on agricultural activities. the however developed some mitigation strategies to cope with food shortages, thus the tendency to reduce the number of meal per day, reduce meal portions, sell of labour, lending and savings groups and cross border trading. The stud also proves that other players including the third sector are involved in supporting the community in coping up with climate change. Challenges in coping to climate have shown that financial constrain is the major challenge and insufficient extension personnel which is a national crisis. The research then ends with recommendations that can be adopted as solutions.